2021
DOI: 10.4254/wjh.v13.i8.939
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular injury and the mortality risk among patients with COVID-19: A retrospective cohort study

Abstract: BACKGROUND Clearly, infection with severe acute respiratory syndrome coronavirus 2 is not limited to the lung but also affects other organs. We need predictive models to determine patients’ prognoses and to improve health care resource allocation during the coronavirus disease 2019 (COVID-19) pandemic. While treating COVID-19, we observed differential outcome prediction weights for markers of hepatocellular injury among hospitalized patients. AIM To investigate the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…We observed a significant difference in AST between survivors and nonsurvivors at hospital admission. The AST-dominant pattern of hepatocellular injury among patients with COVID-19 has been reported many times in previous studies[ 6 , 7 ]. Likewise, the levels of serum ferritin were significantly higher among nonsurvivors.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We observed a significant difference in AST between survivors and nonsurvivors at hospital admission. The AST-dominant pattern of hepatocellular injury among patients with COVID-19 has been reported many times in previous studies[ 6 , 7 ]. Likewise, the levels of serum ferritin were significantly higher among nonsurvivors.…”
Section: Discussionmentioning
confidence: 71%
“…Previously, many reports have cited hepatocellular injury with an aspartate aminotransferase (AST)-dominant pattern at hospital admission[ 6 , 7 ]. In addition, it has been demonstrated that AST elevation at admission is associated with severe COVID-19 disease status and poor outcomes, including intensive care admission, need for mechanical ventilation[ 7 ], and all-cause in-hospital mortality[ 6 ]. It has also been reported that elevated serum ferritin on admission is associated with fatal outcomes in patients with COVID-19[ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the article by “Madian et al [ 1 ]”. Limited data is available for hepatic injury in coronavirus disease 2019 (COVID-19) disease.…”
Section: To the Editormentioning
confidence: 99%
“…For example, the numeric value for serum AST has been incorporated in clinical calculators created to predict progression from mild or moderate to severe COVID-19 disease[ 57 ]. Moreover, elevated AST has been found to be independently associated with increased risk of death, apart from other markers of hepatic dysfunction[ 29 , 34 , 50 , 58 , 59 ]. In a study including 206 patients across 26 institutions in Brazil, AST level greater than twice the upper limit of normal significantly increased the risk of in-hospital mortality when adjusted for age and biologic sex[ 29 ].…”
Section: General Populationmentioning
confidence: 99%